INVESTIGATION OF SHORT-TERM RUTTING PROCESS OF FLEXIBLE PAVEMENT SYSTEM WITH GEOGRID - REINFORCEMENTS BY HOMOGENIZATION METHOD - B. B. Budkowska; J. Yu (International Association of Lowland Technology, 2002)
This paper presents the investigations on short-term rutting that is developed in standard and geogrid-reinforced flexible pavement structure. The main source of the supporting experimental data acquisition on studied type of rutting was provided by laboratory records that had been published in technical literature. The experimental research focused on the development of clear grounds indicating that geogrid-reinforcement is the effective method of reduction of permanent deformations of the pavement system. The comprehensive discussion on the laboratory results showed that the placement of geogrid-reinforcement at various levels of base layer, generated different effects invarious parts of the pavement system. The numerical investigations are focused on determination of modulus of permanent deformation Ep for each layer contributing to the pavement structure. They are considered as being the functions of the number of load repetition N. The constutitutive law incorporated for this purpose is modified 3-D Hooke's law that involves the modulus of permanent deformations. The identification of Ep is-conducted in the framework of homogenization method which assumes the homogenity and isotropy of each layer. The fact of irreversibility of permanent deformations is taken into consideration by geometry's continous updating process. The determination of Ep requires full information on increments of permanent displacements of control points corresponding to each consecutive load repetition. The numerical investigations are performed for axisymetric geometry by means of the finite element analysis (FEA) program ABAQUS (1998). To guarantee the correctness of the results obtained, the problem that was explored was subjected to verivication studies by means of the KENLAYER (1993) program, that was suitably adjusted for this purpose.